National Component of the Training Content of the Teachers in Kazakhstan’s school - Zhampeisova, Korlan; Balykbayev, Takir; Sholpan Kolumbayeva, Natalia Khan; Aitpayeva, Almagul (Opción, 2019)
This study is aimed at revealing and substantiating the national component of the content of pedagogical education and its influence on the development of the national consciousness of the future teacher through the use of an inductively-deductive method and the method of generalization. As a result, the integrating discipline of the national component of the content of pedagogical education is the developed training course National Upbringing Mangilik El. In conclusion, the researchers identified pedagogical conditions that contribute to the effective implementation of the national component of vocational training in the educational process.